Comprehensive analysis of regulatory impacts on performance of Slovak pension funds - Papík, Mário; Papíková, Lenka (Journal of Business Economics and Management, 2021)
Standard pay-as-you-go pension system is facing long-term and short-term sustainability challenges in several countries. Possible replacement of standard pension system might be in a form of private pension savings. Private pension savings are meaningful only if they provide sufficiently high returns. The aim of this manuscript is to analyse performance of Slovak pension funds and factors impacting this performance, especially government interventions. This manuscript is focused on enhanced Carhart four-factor model, Bollen and Busse four-factor model, and Fama and French five-factor model based on 23 pension funds from Slovakia from period starting September 2012 and ending September 2019. These models have been extended by other variables describing bond market factors and impact of regulatory interventions on performance of pension funds. Results of analysis have proved that legislative interventions have impact on performance of analysed pension funds. Each legislative intervention has caused average daily yield to decrease by about 0.01% to 0.03%. Findings described in this manuscript can contribute to better knowledge of pension funds for both contributors who need to decide whether to participate in the second pillar or not, as well as for regulators who develop legislation measurements in this area.